The effect of online marketing and e-service quality on customer loyalty with customer satisfaction as an intervening variable - Wahyu Aji Prabowo; Murry Harmawan; Fitri Rahmawati (Institute of Computer Science (IOCS), 2026)
The primary objective of this research is to analyze the impacts of online marketing and e-service quality on customer loyalty, with customer satisfaction operating as a mediating factor. While digital marketing frameworks are widely explored, empirical focus on localized broadband infrastructures within expanding regional markets remains limited, presenting a distinct research gap regarding telecommunication user behavior. Through a quantitative survey approach, data collection involved 151 IndiHome users based in Kebumen who filled out questionnaires via Google Forms, which were then processed using multiple linear regression analysis via SPSS 25.0. The findings indicate that Online Marketing exerts a positive and significant effect on both Customer Loyalty and Customer Satisfaction. Similarly, E-Service Quality demonstrates a positive and significant impact on both Customer Loyalty and Customer Satisfaction. In addition, Customer Satisfaction significantly influences Customer Loyalty and partially mediates the effects of both Online Marketing and E-Service Quality on Customer Loyalty. These statistical outcomes emphasize that strengthening online promotional frameworks and elevating electronic service delivery are vital to boost user contentment and cultivate sustainable brand allegiance. Consequently, this study implies that PT Telkom IndiHome must continuously refine its digital marketing execution and electronic service infrastructure to preserve consumer satisfaction and maintain long-term loyalty within an increasingly competitive broadband sector